Efektivitas Keluarga Utama Berakhlaqul Karimah Dalam Pemberdayaan Sumber Daya Manusia - Mutiara Nisa; Saeful Anwar (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2020)
The purpose of this study was to find out about the Kampung Kuba program, especially those carried out in Andir RW 09 Cibiuk Village, to know the processes of activities that took place as well as the results felt by the people. The research method used is a descriptive method with a qualitative approach. It is known that the Kampung Kuba program is an empowerment to increase cooperation, strengthen intimacy and encourage young people to be more active, the main goal of which is to realize a society of morality and mercy. The stages include initial socialization, community consultation, and implementation of activities. In the process of carrying out its activities, it is not done officially but the community is given an explanation of the program through activities that have become a habit of the community, such as in the recitation forums for example. The results obtained are changes in the community such as the emergence of the effectiveness of cooperation such as mutual cooperation, although the change is not significant.